The Predictive Ability of Social Media Addiction and Social Isolation in Loneliness among Al-Quds Open University Students - Shaheen, Mohammed Ahmed; Aldeek, Ilham Omar (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the predictive ability of communication addiction and social isolation in feeling lonely among Al-Quds Open University students, using the descriptive correlational approach, and applying the research tools on a random cluster sample, consists of 282 male and female students. The results show a moderate level for social media addiction, social isolation, and psychological loneliness, with an average of (3.21, 2.66, 2.58), respectively. The results indicates that there are no statistically significant differences in social media addiction, social isolation, and feelings of psychological loneliness, due to: gender, place of residence. The results reveals that there is a direct, statistically significant correlation between feelings of psychological loneliness and both social media addiction and social isolation, where value of the Pearson correlation coefficient is (.440 and.846), respectively. The results show that there is a statistically significant effect of social isolation in predicting the feeling of psychological loneliness. Social isolation shows (71.6%) of the percentage of variation in the feeling of psychological loneliness, i.e., the social isolation variable has an important and fundamental role in predicting the feeling of psychological loneliness, while the social media addiction does not contribute in predicting the level of loneliness. The study recommends the provision of psychological counseling centers in universities to detect students who are addicted to social networks and suffer from psychological loneliness, to provide counseling programs suitable for their needs, and suggesting conducting more research on psychological loneliness and its association with social media addiction in different age groups
Keywords: Social isolation; psychological loneliness; social media addiction; university students